Validation of ASCL1 and LHX8 Methylation Analysis as Primary Cervical Cancer Screening Strategy in South African Women with Human Immunodeficiency Virus. (11th November 2022) - Vink, Frederique J; Meijer, Chris J L M; Lissenberg-Witte, Birgit I; Visser, Cathy; Duin, Sylvia; Snyman, Leon C; Richter, Karin L; van der Merwe, Frederick H; Botha, Matthys H; Steenbergen, Renske D M; Dreyer, Greta
Abstract: Background: Compared with women who are human immunodeficiency virus (HIV) negative, women with human immunodeficiency virus (WWH) have a higher human papillomavirus (HPV) prevalence and increased cervical cancer risk, emphasizing the need for effective cervical cancer screening in this population. The present study aimed to validate methylation markers ASCL1 and LHX8 for primary screening in a South African cohort of WWH. Methods: In this post hoc analysis within the DIAgnosis in Vaccine And Cervical Cancer Screen (DiaVACCS) study, a South African observational multicenter cohort study, cervical scrape samples from 411 HIV-positive women were analyzed for hypermethylation of ASCL1 and LHX8 genes, HPV DNA, and cytology. Sensitivities, specificities, and positive and negative predictive values of primary methylation-based, HPV-based and cytology-based screening were calculated for the detection of cervical intraepithelial neoplasia of grade 3 or higher. Results: Single markers ASCL1 and LHX8 resulted in a good performance for the detection of cervical intraepithelial neoplasia of grade 3 or higher, with sensitivities of 85.9% (95% confidence interval [CI], 78.2%–93.6%) and 89.7% (83.0%–96.5%), respectively, and specificities of 72.9% (67.3%–78.5%) and 75.0% (69.5%–80.5%). Combining markers ASCL1 and LHX8 resulted in a lower sensitivity compared with HPV testing (84.6% vs 93.6%, respectively; ratio, 0.90 [95% CI, .82–.99]) and a higher specificity (86.7% vs 78.3%; ratio 1.11 [1.02–1.20]) and reduced the referral rate from 46.8% to 33.4%. ASCL1 / LHX8 methylation had a significantly higher sensitivity than cytology (threshold, high-grade intraepithelial squamous lesion or worse), (84.6% vs 74.0%, respectively; ratio, 1.16 [95% CI, 1.01–1.32]) and similar specificity (86.7% vs 91.0%; ratio, 0.95 [.90–1.003]). Conclusions: Our results validate the accuracy of ASCL1 / LHX8 methylation analysis for primary screening in WWH, which offers a full-molecular alternative to cytology- or HPV-based screening, without the need for additional triage testing. Abstract : This post hoc analysis within a South African observational multicenter cohort study shows that ASCL1 / LHX8 methylation analysis for primary screening in women living with human immunodeficiency virus offers a full-molecular alternative to cytology- or human papillomavirus–based screening, without the need for additional triage testing.